A monolingual approach in an English primary school: practices and implications. (1st November 2022) - Gundarina, Olena; Simpson, James
Abstract: This paper investigates a monolingual approach to the teaching of linguistic minority pupils in an English primary school at Key Stage Two (7–11 years old). The work is based on a longitudinal case study of one Russian-speaking migrant pupil and her schooled experience. The analysis and discussion explicate the prohibition of the first or home language (Russian) in the school, and reveal how denying a seven-year-old migrant child permission to use her L1 is detrimental to her learning experience and her well-being. The focal data derive from participant-observation fieldnotes, visual artefacts and interviews with the child, her mother, and a class teacher over a 7-month period. Through an analysis of the participants' stancetaking, we show how the pupil's voice is inaudible in her struggle against a monolingual attitude towards her bilingualism and multicompetence. Our contribution therefore builds on work in critical migrant language education, to identify the importance of enabling the presence of the L1 in learning for migrant pupils.